2017
DOI: 10.1080/10942912.2017.1369102
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon and its derivatives as potential ingredient in functional food—A review

Abstract: Cinnamon has been reported to have significant benefits for human health, particularly as an anti-inflammatory, antitumor, anticancer, antidiabetic, and anti-hypertriglyceridemia agent, mainly due to its phytochemical constituents such as phenolic and volatile compounds. The phytochemicals in cinnamon can be extracted from different parts of plant by distillation and by solvent extraction. The use of cinnamon in food and its ability to prevent oxidation and inhibit microbial growth are covered in this review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 168 publications
(216 reference statements)
3
66
0
3
Order By: Relevance
“…The price acts as an incentive to harvest more substantial quantities of cinnamon, so it needs to be addressed through sustainable harvesting interventions. Harvesting of the bark of cinnamon is usually done in the rainy season from September-February, which is intended to skin the tree easily [24]. Most of the trees that were observed in the research location are between 8-25 years, which are ready to harvest.…”
Section: Resultsmentioning
confidence: 99%
“…The price acts as an incentive to harvest more substantial quantities of cinnamon, so it needs to be addressed through sustainable harvesting interventions. Harvesting of the bark of cinnamon is usually done in the rainy season from September-February, which is intended to skin the tree easily [24]. Most of the trees that were observed in the research location are between 8-25 years, which are ready to harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research revealed that cinnamon contained ash (2.4%), crude protein (3.5%), crude fat (4%), crude ber (33.0%), moisture (5.1%), carbohydrates (52.0%) and polyphenolic compounds especially avonoids. [32][33][34] However, a quantitative analysis of the phytochemical substances of GIAE revealed the abundance in particular of tannins but low amount in bers and carbohydrates. 31 Added to that, the comparative phytochemical investigation by HPLC-PDA/ESI-MS showed that the main phenolic compounds of ACCE are trans-cinnamic acid, quinic acid, protocatechuic acid, rosmarinic acid, epicatechin and p-coumaric acid, while gallic acid, quinic acid, protocatechuic acid, p-coumaric acid, syringic acid and naringin constitute the predominant chemical components in GIAE.…”
Section: Discussionmentioning
confidence: 99%
“…In the digestive tract, cinnamon has an anti-tumor activity in colon cancer and has been reported to decrease the risk of a gastric ulcer as well as protecting the gastrointestinal system from free radical damage. 8,9 Quercus ilex L. (the evergreen oak) belongs to the family of Fagaceae, and is distributed throughout France, Italy, Croatia, Greece and North Africa, including Morocco, Algeria and especially in northern Tunisia. Oak kernels are traditionally used throughout Tunisia, and other countries, for treating diarrhea and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the common HBAs include salicylic acid, 4-hydroxybenzoic acid, protocatechuic acid, gallic acid, vanillic acid, isovanillic acid and syringic acid. Cinnamon bark contains protocatechuic acid, salicylic and syringic acids (Muhammad and Dewettinck, 2017). Gallic acid is found in clove buds along with protocatechuic acid, p-hydroxybenzoic acid and syringic acid (Tomás- Barberán and Clifford, 2000a).…”
Section: Hydroxybenzoic Acid Derivatives (Hba)mentioning
confidence: 99%